1998
DOI: 10.1074/jbc.273.10.5615
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Second and Third Intracellular Loops of Metabotropic Glutamate Receptors in Mediating Dual Signal Transduction Activation

Abstract: On the basis of sequence homology and structural similarities, metabotropic glutamate receptors (mGluRs), extracellular Ca 2؉ -sensing receptor, ␥-aminobutyric acid type B receptor, and pheromone receptors are enlisted in a distinct family within the larger G proteincoupled receptor superfamily. When expressed in heterologous systems, group I mGluRs can activate dual signal transduction pathways, phosphoinositides turnover and cAMP production. To investigate the structural basis of these coupling properties, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
142
1
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(152 citation statements)
references
References 50 publications
7
142
1
2
Order By: Relevance
“…10, B and C) identifies a subset of residues that may be important for activation of G q/11 by mGluR1 and mGluR5. The importance of the intracellular loops and C terminus has been well documented in previous reports, with the second intracellular loop reported to be necessary but not sufficient for G protein specificity (44,48).…”
Section: Discussionmentioning
confidence: 92%
“…10, B and C) identifies a subset of residues that may be important for activation of G q/11 by mGluR1 and mGluR5. The importance of the intracellular loops and C terminus has been well documented in previous reports, with the second intracellular loop reported to be necessary but not sufficient for G protein specificity (44,48).…”
Section: Discussionmentioning
confidence: 92%
“…The splice variants GABA B 1a and GABA B 1b differ by a 117-aa stretch that is missing at the N terminus of GABA B 1b: this region contains amino acid motifs, termed ''Sushi repeats,'' thought to be involved in proteinprotein interactions (54). The regions involved in coupling the metabotropic glutamate receptors to G proteins are thought to be the second and third intracellular loops (55)(56)(57), so it might be likely that the same applies to GABA B receptors (58). However, we have clearly shown that GABA B 1aϩ2 receptors have a different G ␣ coupling profile to the GABA B 1bϩ2 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The group I mGluR family can interact with the cAMP cascade through a G protein mechanism (Thomsen 1996;Balazs, Miller et al 1998) involving Gs and Gq (Tateyama and Kubo 2006). The coupling of the mGluR1 receptor to a given cascade has been localized to the carboxy terminal (Gabellini, Manev et al 1993) and to intracellular loops two and three (Francesconi and Duvoisin 1998). Further studies are necessary to determine whether the cAMP and mGluR mechanisms occur in series or in parallel (Kelley, Davidson et al 2007).…”
Section: Cyclic Amp Theory Of Fragile Xmentioning
confidence: 99%